A gravidade da (in) imputabilidade penal dos menores nas legislações do Brasil e do Paraguai - Segovia, Aldo Rene (2017)
This study addresses the social and political implications that affect criminal minority, especially considering the geographical position of minors in relation to the border between Brazil and Paraguay. The objective of the study is to carry out a comparative analysis of the legislation related to minors in Brazil and Paraguay, since we live in times of globalization and, although Mercosur has been a reality since the 1990s, the system of protection for minors still Does not count with efficiency in the treatment destined to the minor offenders. The large number of minors involved in the contravention leads many political actors to raise the possibility of reducing the age of criminality, demonstrating that punishment can help to reduce criminality among minors. Thus, the comparative study of Brazilian and Paraguayan legislation offers a view that it is necessary to create mechanisms for the prevention and resocialization of juvenile offenders in order to reduce public expenditures with juvenile detention and punishment with detention, since they collaborate to That juveniles become more efficient in crime when they become adults. The analysis of criminal responsibility contributes to defining the limits of punishment to juvenile offenders and to identifying the best measures in the fight against teenager crime.